Perbandingan Analisis Kemampuan Literasi Matematika Siswa Kelas VII di SMP Negeri 3 Lengayang - Antoni Rahman; Yanti Nazmai Eka Putri; Ratna Mayang Sari (Kilau Publishing, 2025)
Abstract This study aims to analyze and compare the mathematical literacy skills of seventh-grade students at SMP Negeri 3 Lengayang between class VII A and class VII B. Mathematical literacy refers to an individual’s ability to formulate, apply, and interpret mathematics in various real-life contexts. This research employed a quantitative approach using a descriptive comparative method. The research instrument was a mathematical literacy test consisting of contextual essay questions developed based on the Programme for International Student Assessment (PISA) mathematical literacy indicators. The data were analyzed using descriptive statistics and an independent samples t-test. The results showed that the average mathematical literacy score of students in class VII A was higher than that of students in class VII B. The t-test results indicated that the calculated t-value exceeded the critical t-value at the 0.05 significance level, indicating a significant difference in mathematical literacy skills between students of class VII A and class VII B. Keywords: mathematical literacy, comparative analysis, t-test, junior high school students.